Histórias em quadrinhos: propostas de leitura e retextualização - Lima, Izabel de (2021)
With the advent of computing, more than two decades ago, the verbal and non-verbal languages are in evidence in multimodal texts that circulate in society. In this scenario, according to the National Common Curricular Base (BNCC 2017), it’s up to the school to promote skills development and reading and writing competences, from the study of textual genres, for the learning of several linguistic knowledge, in order to guarantee an integral education and maker of protagonists citizens of knowledge. In light of this learning and acquisition of learning proposal, the present report puts forward the first application of Pedagogy Notebook activities entitled Comic Books: Reading and Retextualization Proposals, in a sixth-grade classroom of elementary school. The structure of the Notebook is grounded, theoretical and methodologically, in the model of Didactic Sequence (DS) by Dolz Noverr and Schneuwly (2004), which presents a work scheme initiating with the Presentation of the situation and afterwards with the steps: initial Production, Module I, Module II and final Production. It’s also based on Marcuschi’s conceptualizations (2010), which claim to be, speech and writing, part of the literacy process. Cintra and Passarelli (2011), presenting emphatically the reading as a means of transforming the individual reader. Dell’ Isolda (2007), standing out that retextualization doesn’t have to be mechanics, once that it’s daily practice, since the prosaic speech situations until the achievement of academic works. The linguistic researchers Nascimento, Oliveira e Ribeiro (2015) stress the importance of the teacher, since the beginning of writing process, in the choice of produced genre until the moment of production, evaluation and textual refraction. It’s also used the Grammarians Almeida (2009); Bechara (2015, 2019), Perini (2005, 2014). The application of the Didactic Sequence (DS) activities was accomplished through remote or in-person classes, through WhatsApp, Podcast support and videos on YouTube, due to the pandemic of the new coronavirus, SARS-CoV-2, since March the 11th 2020, in Brazil. In this class modality, the ativicty of the last step, the final Production, couldn’t be applied.